Bulletin 67 Electric Furnaces Making Iron and Steel - Dorsey A. Lyon; Robert M. Keeney (The National Institute for Occupational Safety and Health (NIOSH), 1916)
In the inquiries and investigations that the Bureau of Mines is making with a view to increasing safety, efficiency, and economic development in the metallurgical industries, the application of elec- tricity to various processes, and especially to those in the manu- facture of iron and steel, is being given attention. Some results of the work already done are presented in this bulletin, which gives a historical review of the development of electric furnaces for making iron and steel, and discusses the problems that remain to be solved in the use of electric furnaces for the smelting of iron ores and the production of pig iron at a profit on a commercial scale.